Firm growth types and key macroeconomic aggregates through the economic cycle - Došenović Bonča, Petra; Tajnikar, Maks; Ponikvar, Nina; Mörec, Barbara (Journal of Business Economics and Management, 2018)
The paper investigates the role and impact of different groups of firms according to their growth type on macroeconomic aggregates at various stages of the economic cycle based on the entire population of firms in Slovenia. The applied classification of growing and fast-growing firms is based on microeconomic theory. Results exhibit that despite larger year-to-year fluctuations, firms with growth towards their long-term equilibrium contributed most to macroeconomic aggregates, i.e. employment, capital and sales, especially in times of economic prosperity. Firms with growth that shifts them closer to their short-term equilibrium proved to be more important primarily for assuring employment stability. Furthermore, we show that using single growth measures prevents us from identifying all growing firms and capturing the true contribution of particular growth groups of firms to studied macroeconomic aggregates. The paper provides both theoretical and empirical information for managers for designing different types of firm growth and enables policy makers to adopt adequate industrial policy measures.